INFLUENCIA DE LA FRECUENCIA DE LOS ESTIMULOS SOBRE LA ACCION BRADICARDICA DEL VAGO - POZO, EFREN C DEL (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1947)
Vital staining expts with cats show that for increased vascular permeability of the cortex of the brain it is necessary to have a lesion of the cerebral tissue or compression of the edematous tissue at a hole in the skull It is not necessary that this
BOL INST ESTUD MED BIOL
Keywords: INFLUENCIA, FRECUENCIA, ESTIMULOS, ACCION, BRADICARDICA, VAGO; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA